2014
DOI: 10.1136/bmjopen-2014-005330
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with failure of enhanced recovery protocol in patients undergoing major hepatobiliary and pancreatic surgery: a retrospective cohort study

Abstract: ObjectiveThis study examined the risk factors associated with failure of enhanced recovery protocol after major hepatobiliary and pancreatic (HBP) surgery.Setting and participantsA retrospective cohort of 194 adult patients undergoing major HBP surgery at a university hospital in Hong Kong was followed up for 30 days. The patients were from a larger cohort study of 736 consecutive adults with preoperative urinary cotinine concentration to examine the association between passive smoking and risk of perioperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
16
1
1
Order By: Relevance
“…Postoperative complications that led to deviations from the proposed pathway generally concerned drains, nutrition, and supplementary investigations, and were adapted according to clinical evaluation. A recently published retrospective cohort study identified factors associated with "failure" of a HPB pathway [ 23 ], defined as length of stay in the intensive care unit (ICU) more than 24 h after surgery, unplanned admission to ICU within 30 days, readmission to the hospital within 30 days after surgery, reoperation for complications and/or 30-day mortality. Predictive factors of ERP failure were smoking, high preoperative alanine transaminase/glutamicpyruvic transaminase concentration (defined as more than 67 IU/L in men and more than 55 IU/L in women), or postoperative complications.…”
Section: Bowel Movement Stimulationmentioning
confidence: 99%
“…Postoperative complications that led to deviations from the proposed pathway generally concerned drains, nutrition, and supplementary investigations, and were adapted according to clinical evaluation. A recently published retrospective cohort study identified factors associated with "failure" of a HPB pathway [ 23 ], defined as length of stay in the intensive care unit (ICU) more than 24 h after surgery, unplanned admission to ICU within 30 days, readmission to the hospital within 30 days after surgery, reoperation for complications and/or 30-day mortality. Predictive factors of ERP failure were smoking, high preoperative alanine transaminase/glutamicpyruvic transaminase concentration (defined as more than 67 IU/L in men and more than 55 IU/L in women), or postoperative complications.…”
Section: Bowel Movement Stimulationmentioning
confidence: 99%
“…The definition of ERAS protocol failure used for the pupose of this study was also based on a composite measure described previously 13 and included any one of the following events: length of intensive care units (ICU) admission >24 h immediately after surgery; unplanned ICU admission within 30 d after surgery; unplanned hospital readmission within the 30 d after surgery; reoperation for complications within the 30 d following surgery; and 30-d mortality.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…6 However, despite the best efforts of both clinicians and patients, there will be some patients who will either deviate from the ERAS protocol or fail ERAS' key goals. For those patients undergoing cardiac, 9 colorectal, [10][11][12] and hepatobiliary surgery, 13 models have been created to identify variables that may result in either deviation or failure. There have been no such efforts for those patients undergoing PD.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[6][7][8][9][10][11][12] The drastic decline in operative morbidity and mortality is attributed to improvements in meticulous patient selection, surgical techniques and equipment, as well as perioperative care. [8,[13][14][15][16] It is also attributed to the early detection and removal of smaller hepatomas. [17] In the recent two decades, minimally invasive surgery was introduced initially for cholecystectomy and has further extended its application to hepatectomy.…”
Section: Introductionmentioning
confidence: 99%